Conformable Ultrasound Breast Patch - The Future of Breast Cancer Screening? - Andreas Giannakou; Canan Dagdeviren; Tolga Ozmen (European Journal of Breast Health)
Breast cancer is the most common cancer type among women worldwide with an average lifetime risk of 12.9%. Early detection and screening are the most important factors for improved prognosis and mammography remains the main screening tool for the average risk patients. Ultrasound (US) is used in women with elevated breast cancer risk, younger patients and patients with extremely dense breasts. Conventional US has certain limitations including operator dependence and reported low specificity. We designed a conformable US device (cUSBr-Patch) which offers large-area, deep tissue scanning and multi-angle, repeatable breast imaging. It is able to detect lesions as small as 1mm with excellent accuracy and reliability validated by in vivo comparison with conventional US. This is a user-friendly, innovating device designed to be used by patients with the potential to reshape our approach to breast cancer screening.